Analysis of the Kuznets curve relationship between economic development and ecological environment in Aba Prefecture. - Xinglin Liu; Jing Zhou (PLoS ONE)
Background The Yangtze and Yellow River basins play a critical role in China's economic and social development as well as ecological security. As a key ecological barrier in the upper reaches of these rivers, Aba Prefecture has faced questions about whether its economic development after the 2008 earthquake has impacted its ecological environment. Objective This study uses the Environmental Kuznets Curve (EKC) to analyze the relationship and characteristics between per capita GDP and the ecological environment in Aba Prefecture from 2010 to 2021. The aim is to provide scientific evidence for promoting the coordinated development of the economy and environment. Methods The analysis employed the ADF test, Engle-Granger cointegration analysis, and correlation tests on the data. Finally, regression curve fitting was used to derive the relationship between per capita GDP and key environmental indicators in Aba Prefecture. Results Per capita GDP in Aba Prefecture is highly negatively correlated with industrial wastewater discharge, highly positively correlated with domestic sewage discharge, positively correlated with industrial solid waste generation, and uncorrelated with industrial dust emissions. There exists a long-term equilibrium relationship between per capita GDP and both industrial wastewater discharge and industrial solid waste generation, indicating mutual influence and co-variation over time. The EKC curve in Aba Prefecture does not fully align with the traditional EKC model. Specifically, the relationship between per capita GDP and industrial wastewater discharge exhibits an "N" shape, while the relationships with industrial solid waste generation and domestic sewage discharge are linear and upward. There is no relationship between per capita GDP and industrial dust emissions. Conclusion The relationship between the economy and the environment in Aba Prefecture exhibits a certain level of complexity. To achieve a long-term win-win outcome of both economic growth and environmental protection, it is essential to further deepen the transformation of the industrial structure, strengthen environmental governance measures, and optimize policy implementation.